Panorama das capacidades institucionais municipais para a promoção da Governança Ambiental no Estado de São Paulo - Calderan, Andre Mafra (2023)
Studies on the perspective of sustainable development fulfill local governance as central to the promotion of this new development paradigm. However, due to several factors, such as the limitation inherent to the capabilities of public authorities in providing answers to the complex range of environmental issues and problems; the recent institutionalization of specific organizational structures for the Environment agenda in the State of São Paulo or their absence, the institutional structures of local governments still seem to lack sufficient power in promoting environmental governance. To understand this scenario, the present work analyzes the panorama of institutional resources for the promotion of environmental governance in the State of São Paulo. The methodological proposal is divided into two parts: in the first, a critical review of the recent literature on environmental governance in Brazilian municipalities was carried out, from which the main paradigms related to the construction of environmental governance in the national scenario were identified from the understanding of the scale of the concept (global, territorial and local). At this stage, the different meanings of the same concept were reported, even if at different scales of understanding they delimit the construction of environmental governance in municipalities through different strategies and instruments; the second part was carried out based on the survey, systematization and analysis of secondary data from the Munic survey (2021) organized by the Brazilian Institute of Geography and Statistics, with the objective of bringing the paradigms evidenced in the construction of the concept of governance closer to the proposed scenario for the State of São Paulo. In this stage, a series of data correlations are developed on the institutional resources of the municipalities and their environmental management structures, which were divided into: i) capability to promote expanded participation; ii) capability to provide resources; iii) policy coordination capability and means of implementation. Throughout the analyses, critical reflections were proposed on the listed resources and the understanding of municipal environmental governance. As main results, it is highlighted, in the first instance, that the promotion of environmental governance in the State of São Paulo finds as its main challenge the limits of the current model of representative democracy itself, which imposes barriers to the legitimation of participatory practices, opening room for manipulation and to clientelistic practices, which reinforce social exclusion. Thus, understanding the institutions beyond their structures, and considering the rules, norms and the modus operandi of the institutions, it is necessary to improve the institutional capability of the municipalities in the sense of environmental democracy, based on the pillars of participation, access to information and justice, to be able to promote environmental governance.